Anion-induced N-doping of naphthalenediimide polymer semiconductor in organic thin-film transistors - Yang Han (Nature Portfolio, 2018)
Organic electronics: Conjugated polymer doped by fluoride anion Fluoride anions have been confirmed to be capable of n-dope the organic semiconductors and thus provide more possibilities in molecular doping. A collaborative team led by Martin Heeney from Imperial College London shows an effective n-doping effect in P(NDI2OD-T2) polymer by the Lewis basic anion fluoride. The formation of radical anions is confirmed by electron paramagnetic resonance and absorption spectroscopy. Furthermore, the doping effect is verified with the improved characteristics of the thin film transistors such as reduced injection barrier, contact resistance and hysteresis. This anion doping method can be generalised to other halide anions, thus overcoming the problem of poor stability for the conventional ‘charge transfer’ doping. It opens up new opportunities for simple solution processed doping strategies and optimisation of organic electronic devices.